Potential value of differentially expressed circular RNAs derived from circulating exosomes in the pathogenesis of rat spinal cord injury - Zan, Chunfang; Li, Jianan; Lin, Fengsong; Wang, Zengliang (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) remains one kind of devastating neurological damage, and specific molecular mechanisms involved need to be understood deeply. Currently, circular RNAs (circRNAs), as a newly discovered type of non-coding RNAs (ncRNAs), have been under active investigation. Through functional interactions with disease-associated microRNAs (miRNAs), exosome-derived circRNAs have been extensively implicated in various organ pathogenesis. Nevertheless, the functional involvement of circulating circRNAs in SCI onset, progression as well as repair remains poorly explored until now. Of note, there still lacks clinical and experimental evidence in this regard. To obtain some relevant knowledge in this field, this study was originally designed to have a general overview of differentially expressed circRNAs derived from circulating exosomes in SCI rats in comparison with the control rats. It turned out that 709 types of downregulated circRNAs and 346 kinds of upregulated circRNAs were preliminarily screened out. Functional enrichment analyses including KEGG pathway and Gene Ontology were performed to evaluate the possible biological functions of upregulated as well as downregulated circRNAs involved in SCI. Furthermore, five types of upregulated circulating circRNAs including chr4:208359914-208362182+, chr15:20088296-20092102+, chr1: 175098934-175134845-, chr1:175099657-175128203- and chr1:175104454- 175134845-, and plus five kinds of downregulated circulating circRNAs including chr11:74154652-74159524-, chr12:45412398-45412635-, chr7:137630261- 137648924-, chr6:6280974-6281188+ and chr4:225251864-225254087+, were verified through RT-PCR. At last, taking these differentially expressed circRNAs in the center, the circRNA-miRNA-mRNA gene interaction network was constructed to predict the possible functionalities of circRNAs in SCI through anticipating specific interactive miRNAs, giving new insights into how circRNAs contribute to this pathological process. Taken together, these findings suggest the possible involvement and functional significance of circRNAs in SCI.